1972
DOI: 10.1149/1.2404376
|View full text |Cite
|
Sign up to set email alerts
|

Optical Response in the Photoselective Metal Deposition (PSMD) Imaging System

Abstract: The optical response of a representative PSMD imaging system, stannous chloride sensitized polyimide film, was determined by exposing sensitized substrates to ultraviolet radiation and measuring the resulting decrease in catalytic activity for electroless copper deposition. This activity was determined by measuring light transmission through the deposited metal and substrate.The imaging reaction photoresponse was measured in the 200–400 nm wavelength range. The sensitivity was found greatest at 200 nm, decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

1972
1972
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 0 publications
2
20
0
Order By: Relevance
“…The maximum surface height of the film with respect to the underlying glass surface (Figure 3d) is 7 nm, comparable to the size of SnOx nanoparticles observed in other studies [7,8,27]. This implies that the stamped sensitizer film on glass is made up of roughly a monolayer of SnOx nanoparticles.…”
Section: Controlled Deposition Of Sensitizing Snox Nanoparticlessupporting
confidence: 83%
See 2 more Smart Citations
“…The maximum surface height of the film with respect to the underlying glass surface (Figure 3d) is 7 nm, comparable to the size of SnOx nanoparticles observed in other studies [7,8,27]. This implies that the stamped sensitizer film on glass is made up of roughly a monolayer of SnOx nanoparticles.…”
Section: Controlled Deposition Of Sensitizing Snox Nanoparticlessupporting
confidence: 83%
“…Dissolved oxygen in such solutions partially oxidizes the Sn 2+ producing its hydrated oxides that ripen by the sol-gel process to form SnOx (x < 2) nanoparticles. Unfortunately, the formation of complex oxychlorides, oxides of mixed Sn oxidation states, and the influence of dissolved oxygen on its colloidal structure [5,7,8] prevent monitoring of the growth, or even determination of the chemical composition of the SnOx particles in solution. It is also known [27][28][29] that the size of SnOx nanoparticles in the aqueous solutions depends strongly on pH [30].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Weiner and Schiele (4) have shown that the chromic oxide film that forms in potential region I contains only Cr203 with some traces of the cathode metal.…”
mentioning
confidence: 99%
“…Surface activation can then be performed using two main processes known as ''two-step'' or ''one-step'' processes. In the former case [27][28][29][30], the oxidized substrate surface is first sensitized by immersion in an acidic tin chloride (SnCl 2 ) solution and then activated by immersion in an acidic palladium 692 F. Bessueille et al…”
Section: Electroless Depositionmentioning
confidence: 99%